Dificultades en la producción oral en Inglés intermedio intensivo de segundo año de profesorado del idioma inglés - Bernal Lemus, Kevin Armando BL17007; Magaña Quijano, Ivania Stefany MQ17019; Mauricio Benítez, Kevin William MB17008 (2025)
The ability to express oneself and communicate successfully in spoken English is referred to as oral production. It is defined as the process of producing spoken language in daily real-time encounters, such as conversations, presentations, interviews, or other forms of oral communication. This paper research presents an investigation on the difficulties in Oral Production of the students attending the Second Year course of Teaching in English at the University of El Salvador (FMO) Semester II-2023, whose objective is to determine what is causing the difficulties that students are facing day by day, also to find a way to minimize such difficulties and find results that may lead to gather useful data for analysis and further researchers as well as being beneficial for the population under study. In addition to this, throughout this investigation we were using the quantitative method, and the results were presented in the form of percentages and graphics, once given the results, the study showed that the oral production of the students is being affected by four main factors: their level of grammatical knowledge, lexical knowledge, intonation and lack of pronunciation skills. The results of this investigation are going to help improve the quality of spoken English in second year students, as it shows what is causing the current deficiency they have. Another key factor of this research is that some recommendations were given for students and teachers, because it is stated that in the process of improving the competences in the language efforts from both parties are involved and need to be worked together.